ISCR2 and IS26: Two Insertion Sequences Highly Dispersed among Acinetobacter spp. Clinical Strainss - Montaña, Sabrina Daiana (2017)
The aim of this work is to study the dispersion of two ISs, ISCR2 and IS26, which are known to contribute in the acquisition of resistance determinants and genome plasticity, among a collection of hundred and seventy-four Acinetobacter spp. clinical isolates. PCR amplification reactions using total DNA were performed to search ISCR2, IS26, and different antibiotic resistance genes (tet(B), aphA6, sul2, floR, dfr9) previously described in the genetic context of ISCR2.Among A. baumannii, positive amplification for ISCR2 was obtained in 66% of the included isolates and most of them (93%) were positive for IS26 amplification. The platform tet(B)::ISCR2 was found in 57% of the ISCR2 positive isolates and only 14 gave negative amplification for tet(B). In these isolates positive amplifications of genes that were previously described associated to ISCR2 -such as, aphA6, sul2, floR, and dfr9- were observed. When searching these ISs in the non-baumannii Acinetobacter studied-collection, two isolates were positive for ISCR2 and two isolates for IS26. No positive results were obtained for tet(B), but the presence of sul2, floR and dfr9 was found. Our results exposed a great dispersion of ISCR2 as well as IS26 among Acinetobacter spp. clinical isolates reinforcing the idea that the ISs play a crucial role in the plasticity and evolution towards drug resistance in this genus.